HUBUNGAN PERILAKU DAN LINGKUNGAN RUMAH DENGAN TB PARU DI WILAYAH KERJA PUSKESMAS PANYABUNGAN JAE - Kurnia alamsyah Alamsyah; Santy Deasy Siregar (Fakultas Kesehatan Masyarakat Universitas Prima Indonesia, 2020)
ABSTRACT Pulmonary tuberculosis or pulmonary tuberculosis is a contagious infectious disease that attacks the lungs and bronchi. This disease is caused by mycobacterium tuberculosis which spreads through the air of human respiratory discharges. In 2017, the figure of Case Notification Rate / CNR (new case) of pulmonary TB (+) in North Sumatra was 104.3 / 100,000 population and Mandailing Natal District became an area second place with CNR of 187 / 100,000 population. One of the factors that can affect the recovery of pulmonary TB include behaviors such as knowledge, attitudes and actions as well as the environment such as ventilation area and occupancy density. The purpose of this study was to determine the relationship of behavior and home environment to the incidence of pulmonary TB in Panyabungan Jae Public Health Center in 2019. This type of research uses analytic survey method with cross sectional approach. The sample in this study were 56 people taken by total sampling technique. The results showed that the majority of respondents have less knowledge, negative attitudes, actions are not good, the area of ​​ventilation of the house does not meet the requirements and the density of dense occupancy with the majority of the occurrence of pulmonary TB. Bivariate test results found that there is a relationship between knowledge (p = 0.003), attitude (p = 0.010), actions (p = 0.013), ventilation area (p = 0.003) and density (p = 0.017) with the incidence of pulmonary TB in the Panyabungan Jae Public Health Center. It is expected that the community in the Panyabungan Jae Puskesmas area will be more active in carrying out the examination and treatment of new TB and following the management of pulmonary TB provided by health care workers. The next researcher is expected to be able to develop research on the factors that cause pulmonary TB in a region